Aluminum diffusion inhibiting properties of Ti5Si3 at 900 °C and its beneficial properties on Al-rich oxidation protective coatings on γ-TiAl. (June 2022) - Bauer, Peter-Philipp; Swadźba, Radosław; Klamann, Lisa; Laska, Nadine
Abstract: The goal of the paper was to elucidate the effect of a Ti5 Si3 interlayer on the high temperature oxidation resistance of the Al-Ti coatings. During cyclic oxidation at 900 °C for 1000 1 h cycles, the coating system with a Ti5 Si3 interlayer maintained the Al-rich phases of TiAl3 and TiAl2 in the Al-Ti top layer around 5–10 times longer compared to a coating without intermediate barrier layer. Moreover, the substrate alloying elements (Nb and Cr) are suggested to have a noticeably positive impact on the reduced Al diffusion due to segregations at the grain boundaries in the Ti5 Si3 interlayer. Highlights: Al-30Ti/Ti-38Si coatings provide excellent oxidation resistance to γ-TiAl at 900 °C. Ti5 Si3 acts as a diffusion barrier reducing Al depletion in the coating. Cr and Nb effect the diffusion inhibiting properties of the Ti-Si layer. Phase and microstructural transformations analyzed by HT-XRD, STEM and SEM.